2018
DOI: 10.1016/j.heliyon.2018.e00889
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of access and utilisation of seasonal climate information services among smallholder farmers in Makueni County, Kenya

Abstract: Climate change is a major development challenge in sub-Saharan Africa. This region is highly vulnerable to negative impacts of climate change due to low adaptive capacity and overreliance on rain-fed agriculture for food security and livelihood. Climate information services (CIS) have been developed in Kenya to help enhance farmers' adaptation to climatic shocks, but their access and utilisation remain low. The factors that influence farmers' access and use of CIS are not well-known. Using survey data from a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 21 publications
11
67
1
Order By: Relevance
“…This indicated that farmers who own television sets are able to access more agricultural programmes on conservation agriculture and agroforestry than those without. The finding corresponds to Muema et al (2018), who observed that broadcasting agricultural programmes through television stations could strongly impact farmers. The results further showed that farmers' accessibility to radio had a significant negative influence on the adoption of crop diversification by 8.2%.…”
Section: Determinants Of Smallholder Farmers' Adoption Of Adaptation Technologiessupporting
confidence: 82%
See 1 more Smart Citation
“…This indicated that farmers who own television sets are able to access more agricultural programmes on conservation agriculture and agroforestry than those without. The finding corresponds to Muema et al (2018), who observed that broadcasting agricultural programmes through television stations could strongly impact farmers. The results further showed that farmers' accessibility to radio had a significant negative influence on the adoption of crop diversification by 8.2%.…”
Section: Determinants Of Smallholder Farmers' Adoption Of Adaptation Technologiessupporting
confidence: 82%
“…The third stage involved random selection of 384 households in a proportionate to size manner from a total population of 30,885 small scale farmers in the randomly selected wards. Similarly, the Kenya Agricultural and Livestock Research Organisation (KALRO) in collaboration with the Kenya Meteorological Department (KMD) had over the last three years been disseminating climate change adaptation information using different sources, including radio, short message service (SMS), television and public meetings (Muema, Mburu, Coulibaly, and Mutune, 2018). A sample size of 384 smallholder farmers was determined using the Cochran equation.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, household age was negatively correlated with access to weather information (r ďż˝ − 0.15, p < 0.001). Older farmers have limited social networks and poor interactions with local institutions, which ultimately negatively influences access to climate information [58]. Moreover, Kirui et al [59] underlined that older farmers preferred indigenous knowledge over modern climate information services.…”
Section: Resultsmentioning
confidence: 99%
“…The motivation to use sub-seasonal or seasonal forecasts to manage climate impacts in Machakos and other semiarid areas may also be justified from declining maize and other crop yields relative to decreasing rainfall amounts and rising temperatures in the region (Nyandiko et al, 2014;Kiprotich et al, 2015;Gichangi and Gatheru, 2018). Other determinants of the uptake and use of WCI in the region included access of WCI, age of the household head, farm size, gender and size of the household (Muema et al, 2018), and declines in historical rainfall amounts (Okumu, 2013).…”
Section: Key Factors That Influence the Uptake Use And Adoption Of Weather And Climate Informationmentioning
confidence: 99%